Evaluation of Reasons to Divorce in Divorce Suits Took Place in Istanbul in 1999 - Dişsever, Halim; Dişçi, Rian (The Bulletin of Legal Medicine, 2000)
3060 divorce suits are within the scope of this research, which aims to evaluate the reasons of divorce in Istanbul. Among 3060 divorce suits, 67.1% of them (2053) were brought to an action by women and 32.9% of them (1007) by men. The reasons to divorce according to how frequently they were seen are: severe incompatibility, heavy alcohol consumption, attempt against life, and willful desertion in due respect. a 1.6% of divorced couples (1272) had no child. 40.4% of these couples (12.36) had 5 years of marriage. In case of having a child, the child's guardianship was mostly given to mother due to his/her young age. In 7.6% (2.3.3 > of divorce suits either mother or father was registered to Istanbul as their birthplace, in 28.2% (864) of the suits couples were both registered to Istanbul, and in 64.2% (196.3) of the suits divorced couples were out of Istanbul. Divorced couples and their children have emotional and economic problems after divorce. They also have problems of social security, unemployment, education and subsistence allowance. Therefore, data evaluation proposed that social support mechanisms of the society must be improved.Key Words: Divorce, divorce reasons.
Keywords: divorce; divorce reasons